Ready to respond: adapting rapid response team training in Papua New Guinea during the COVID-19 pandemic - Marsh, Celeste; Salmon, Sharon; Housen, Tambri; Flint, James; Taylor, Joanne; Hapolo, Emmanuel; Ortuzar, Maria Trinidad Velasco; Smaghi, Bernnedine; Eshofonie, Anthony; Ropa, Berry (Western Pacific Surveillance and Response, 2022)
Problem: Rapid response teams (RRTs) are critical for effective responses to acute public health events. While validated training packages and guidance on rolling out training for RRTs are available, they lack country-specific adaptations. Documentation is limited on RRT programming experiences in various contexts. Context: In Papua New Guinea, there remain gaps in implementing standardized, rapid mobilization of multidisciplinary RRTs at the national, provincial and district levels to investigate public health alerts. Action: The human resources needed to respond to the coronavirus disease (COVID-19) pandemic forced a review of the RRT training programme and its delivery. The training model was contextualized and adapted for implementation using a staged approach, with the initiation training phase designed to ensure RRT readiness to deploy immediately to respond to COVID-19 and other public health events. Lessons learned: Selecting appropriate trainees and using a phased training approach, incorporating after-training reviews and between-phase support from the national programme team were found to be important for programme design in Papua New Guinea. Using participatory training methods based on principles of adult learning, in which trainees draw on their own experiences, was integral to building confidence among team members in conducting outbreak investigations. Discussion: The RRT training experience in Papua New Guinea has highlighted the importance of codeveloping and delivering a context-specific training programme to meet a country’s unique needs. A staged training approach that builds on knowledge and skills over time used together with ongoing follow-up and support in the provinces has been critical in operationalizing ready-to-respond RRTs.